Der nicht-reduktive Idealismus von Holm Tetens - Viertbauer, Klaus (Zeitschrift für katholische Theologie, 2018)
While most of the discussion concerning Holm Tetens’s seminal paper Gott denken – Ein Versuch über rationale Theologie (2015) focuses on the theological issues of redemption and theodicy, my paper wants to explore the ontological foundations of Tetens’s panentheism and to demonstrate why Tetens prefers an idealistic to a panpsychist approach. In order to do so, a typology of current ontological positions shall be presented before going on to show that Tetens’s concept is based on a nonreductive type of idealism.